French team demonstrates terahertz transistor. - Hellemans, A.
The creation of a nanotransistor that generates a terahertz signal by means of plasma waves was reported by researchers in France in the 29 March issue of Applied Physics Letters. Such devices could fill a gap between 0.3 and 3 terahertz, for which no compact solid-state sources are available.
Keywords: 0.3 to 3 THz; Montpellier transistor; Electron beam lithography; Nanotransistor; Nonionizing radiation; Plasma waves; Terahertz emission; Terahertz gap; Terahertz signal; Terahertz transistor